Optimalisasi Pengawasan Ombudsman Perwakilan Manokwari Menuju Birokrasi yang Bersih dan Melayani - Naomi Marliani Rumbewas; Marius Suprianto Sakmaf; Meiora Ariella Papare (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2024)
This article discusses the role of the Ombudsman of the Republic of Indonesia (ORI) in achieving good governance in Manokwari Regency. The main issue is the monitoring mechanism implemented by the Manokwari Ombudsman Representative in the execution of public services and the steps taken to improve the effectiveness of oversight. This research aims to understand how the Manokwari Ombudsman Representative oversees public services and the efforts made to enhance the effectiveness of this oversight. The method used is descriptive qualitative research, which focuses on the characteristics, quality, and interrelation of activities. The research results indicate that the Manokwari Ombudsman Representative plays an important role in ensuring the level of public service and preventing maladministration. They are active in receiving and handling reports every year, including those from the public, consultations related to reports, and self-initiated investigations. Additionally, the Ombudsman ensures transparency and accountability in government. However, a significant number of individuals still lack understanding of discrimination in public services, and unclear complaint mechanisms pose challenges when they experience unsatisfactory services.